BAKO : Biodiversity Between Land and the Sea - Mohd Azlan, Jayasilan; Mohamad Kadim, Suaidi; Indraneil, Das (UNIMAS Publisher and Natural History Publications (Borneo) Sdn. Bhd., 2023)
Sarawak’s vast forested landscape includes numerous protected areas network, comprising National Parks represents some of the best examples of the State’s natural wonders- fl oral, faunal as well as geological. Western Sarawak, in particular, is an important area for biodiversity conservation, being home to many Bornean endemics and other species of conservation importance that do not extend beyond the north-western corner of this large tropical island.